Promoting Patient Safety: Examining the Significance of Nursing Documentation - Shamsa Samani; Salma Amin Rattani (Achievements and Challenges of Medicine and Medical Science Vol. 11, 2025)
Background: During hospitalization, receiving safe and competent care is a patient’s right and the healthcare providers’ professional, moral, and ethical responsibility. However, this does not always occur and there remains a gap. This is depicted in two clinical cases that are presented here. Nurses are professionally accountable for assessing and documenting patients’ vital signs. Nurses failing to fulfill this responsibility position their patients at risk. This paper presents two real-life cases pertaining to patients’ safety resulting in fatal outcomes, leading to the professional, legal, and ethical liability of nurses as the providers of patient care. Objective: This paper focuses on the role of organizational culture in fostering patient safety specifically in monitoring and documentation of patients’ vital signs and early recognition of warning signs. Methodology: A comprehensive literature search was conducted using various databases, examining the significance of vital signs monitoring and documentation and early warning signs in patient safety. Relevant articles combining quantitative and qualitative data were analyzed. Results: By fostering an environment of honest reporting, healthcare organizations can enhance patient safety and improve the quality of care. This paper offers valuable insights and recommendations for developing effective strategies aligned with organizational policies and protocols. Conclusion: Assessment and documentation of vital signs is an integral part of nursing practice to communicate patient physiological information to the healthcare team and to provide safe and competent care to patients. This paper serves as a valuable resource, encouraging healthcare professionals to reflect on their practices and the organizations to assess their contributions to creating a culture of safety. It also highlights the importance of reporting and disclosing adverse events as learning opportunities and outlines the role of ethics, professionalism, legislation, and organizational support in achieving patient safety.